Fine Needle Aspiration Cytology Study of Soft Tissue Tumours: A Study of 140 Cases - Kanasagara, Anand; Vaghani, Krishna D (Annals of Pathology and Laboratory Medicine, 2018)
Background: The diagnosis of soft tissue tumours has always been difficult and controversial. The use of fine needle aspiration cytology ( FNAC ) instead of incisional biopsy for the diagnosis of soft tissue tumours was first reported in 1919 and since then has become a very popular cytodiagnostic procedure. Our aim is to study type of soft tissue tumors, age, sex and site distribution, incidence of benign and malignant lesions, to know role of FNAC and its efficacy in diagnosis of soft tissue tumors & compare our results with previous published studies. Methods: Total 140 cases of soft tissue tumors were studied prospectively from september 2013 to november 2015, out of them 31 cases were followed up for cytology-histopathology comparison. Results: Most common site of soft tissue tumors was upper extremities, 91.5% of all the lesions were benign & most common tumor was lipoma. Conclusion: FNAC is a very useful tool for diagnosis of soft tissue tumors, in our study we found that FNAC was 100% accurate in diagnosing malignant tumors, 96% accurate in diagnosing benign soft tissue tumors & 90.3% efficient in identifying whether a tumor is benign or malignant.